Conventional gingivectomy for chronic gingival enlargement in orthodontic treatment: a case report - Irma Dewi Ratnawati; Rosa Pratiwi (Odonto : Dental Journal, 2023)
Background: Gingival enlargement, also known as gingival overgrowth, is an enlargement of the gum tissue. There are many possible causes for enlarged gums. Gingival enlargement is general feature of gingival diseases. It is common note to chronic inflammatory gingival enlargement was caused by poor of oral hygiene. Orthodontic braces can interfere with good oral hygiene, contributing to the development of the inflammatory process. One of the most common soft tissue problems related to fixed orthodontic appliances is gingival hypertrophy or hyperplasia. Maintaining oral hygiene is hindered in cases of gingival hypertrophy due to orthodontic appliances. The most widely used surgical method to treat gingival hypertrophy is gingivectomy. Case Report : A 27-year-old patient was referred to the periodontal clinic of Airlangga University Dental Hospital because of primary gingival swelling with gingival bleeding during brushing in the anterior mandibular region. On intra oral examination showed excessive gingival with probing depth was range 4 mm on teeth 42-32, revealing the presence of pseudopockets. Clinical examination revealed generalized gingival enlargement as well as generalized bleeding on examination. After explaining the condition and treatment to the patient, he was registered for phase I treatment. After evaluating phase I therapies, phase II treatment with gingivectomy and gingivoplasty were required using a scalpel. Conclusion: Conventional gingivectomy gives satisfactory result in treating the inflammatory gingival enlargement.